2017
DOI: 10.1136/bmjophth-2016-000061
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of an extemporaneous preparation of 2% ganciclovir eye drops in CMV anterior uveitis

Abstract: BackgroundTo evaluate the efficacy and safety of an extemporaneous preparation of 2% ganciclovir topical eye drops in cytomegalovirus (CMV) anterior uveitis because many studies have confirmed the benefits of topical ganciclovir in varying concentrations.DesignThe study employed a retrospective cohort design.MethodsThis study enrolled 11 eyes (11 patients) with CMV anterior uveitis. All cases were proved by positive PCR for CMV DNA from aqueous tapping and received topical 2% ganciclovir, applied every 2 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…However, systemic ganciclovir has the risk of systemic side effects including granulocytopenia, thrombocytopenia, and anemia. Recently, many studies have confirmed the benefits of topical ganciclovir for CMV-AU treatment [15][16][17][18]. The concentration of the drug was reported to be 0.15% ganciclovir gel and 0.5% to 2% ganciclovir eye drops.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, systemic ganciclovir has the risk of systemic side effects including granulocytopenia, thrombocytopenia, and anemia. Recently, many studies have confirmed the benefits of topical ganciclovir for CMV-AU treatment [15][16][17][18]. The concentration of the drug was reported to be 0.15% ganciclovir gel and 0.5% to 2% ganciclovir eye drops.…”
Section: Discussionmentioning
confidence: 96%
“…Continuous topical 0.5% ganciclovir eye drop treatment did not cause systemic or ocular complications. No studies have reported significant side effects, such as ocular discomfort or corneal toxicity, with topical ganciclovir treatment [15,17,18]. Continuous 0.5% ganciclovir eye drop treatment may reduce the rate of recurrence of anterior chamber inflammation and result in the avoidance of glaucoma surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Topical ganciclovir and topical prednisolone are used in treating corneal endotheliitis to target both infectious and inflammatory components. Topical ganciclovir 2% was effective and safe for anterior segment inflammation secondary to CMV infection [ 15 - 17 ]. This preparation is beneficial when commercially prepared topical ganciclovir is not widely available.…”
Section: Discussionmentioning
confidence: 99%
“…Non-serious adverse events may include any unfavourable medical occurrences in participants who have ever received study medication, regardless of any causal relationship with treatment. This may include increased intraocular pressure (>24 mm Hg), abnormal laboratory findings (rise in creatinine from ≥1.5 to<2 mg/dL, reduction of white blood cell count to below >1000 to <2500/μL, platelet count from 20 000 to 75 000, or haemoglobin level from >6.5 to <9 g/dL), concurrent accident or illness, increase in the frequency and severity of a pre-existing condition, side effects intolerable to participants (gastrointestinal upset, nausea, vomiting, fatigue), or signs of corneal or conjunctival toxicity (keratitis or conjunctivitis) 23 24 31…”
Section: Methods and Analysismentioning
confidence: 99%
“…Topical ganciclovir 2% has also been used to treat and prevent recurrences of CMV anterior uveitis 20–22. Topical therapy is attractive as it does not require laboratory monitoring, although ocular side effects including corneal epitheliopathy and conjunctivitis could preclude long-term use 23 24. Thus, comparing oral valganciclovir 900 mg two times per day to topical ganciclovir 2% six times per day has equipoise in the uveitis/cornea specialist.…”
Section: Introductionmentioning
confidence: 99%